Seawater temperature drives the diversity of key cyanobacteria (Synechococcus and Prochlorococcus) in a warming sea - Coello-Camba, Alexandra; Agustí, Susana (Frontiers in Marine Science, 2024)
The picocyanobacteria genera Prochlorococcus and Synechococcus play a significant role globally, dominating the primary production in warm and oligotrophic tropical and subtropical areas, which represent the largest oceanic ecosystem. Genomic studies have revealed high microdiversity within these genera. It is anticipated that ocean warming may cause decreased biodiversity in marine tropical areas, as increasing temperatures may lead to the development of a new thermal niche in these regions. Thus, our study aimed to characterize the microdiversity of picocyanobacteria in the Red Sea, one of the warmest oligotrophic seas on the planet, which is experiencing warming at a rate that exceeds the global average. We identified picocyanobacteria microdiversity in the open waters of the Eastern Red Sea basin, where seawater temperatures ranged from 22.2 to 32.4°C throughout the water column (from surface to 160 m depth). Both Prochlorococcus and Synechococcus populations were characterized to deep taxonomic levels, applying amplicon sequencing targeting the petB gene, revealing up to 15 different (sub)clades. Synechococcus dominated the basin, representing an average of 68.8% of the total reads assigned to both cyanobacteria. The subclade Synechococcus IIa and Prochlorococcus clade HLII were ubiquitous in the water column of the Eastern Red Sea basin, representing 73% and 56% of the Synechococcus and Prochlorococcus assigned reads, respectively. Maximum cyanobacteria richness was observed at approximately 27.5°C, declining at higher and lower temperatures (polynomial fit, R2 = 0.2, p<0.0001). Synechococcus IIa dominated in the warmest surface waters (>30°C) of the Red Sea, displacing other (sub)clades to more saline and nutrient-poor waters, thereby reducing community diversity (polynomial fit, R2 = 0.77, p<0.0001). Our study contributes to identifying changes in picocyanobacterial diversity when exposed to temperatures exceeding current oceanic thermal limits, through the analysis of Red Sea communities already inhabiting such higher-temperature niches.